'The Heart of the Country': The Primacy of Peasants and Maize in Modern Guatemala. Issue 2 (26th December 2018) - Carey, David
Abstract: Much of the agricultural history of nineteenth- and twentieth-century Latin America has been dominated by studies of export products and economies. Yet just as important for national development were domestic markets supplied by small-scale farmers. Using Guatemala as a case study for Latin America, this article examines the challenges faced by farmers producing for local, regional and national markets. Over the course of the national period, state authorities' sporadic concern for domestic agriculture provided indigenous small-scale farmers with opportunities to advance their agendas, which ranged from resisting forced labour to maintaining their traditional agricultural practices. By the 1930s, domestic foodstuff production had increased markedly because in the early twentieth century state authorities had joined small-scale farmers to actively promote domestic-use agriculture. Spanish abstract: Mucha de la historia de la agricultura latinoamericana de los siglos XIX y XX ha estado dominada por los estudios de productos de exportación y sus economías. Sin embargo, igualmente importante para el desarrollo nacional fueron los mercados domésticos abastecidos por pequeños agricultores. Utilizando a Guatemala como un estudio de caso para Latinoamérica, este artículo examina los retos que enfrentaron campesinos que producían para los mercados locales, regionales y nacionales. Durante el transcurso del periodo nacional, la preocupación esporádica de las autoridades estatales por la agricultura doméstica proveyó de oportunidades a pequeños agricultores indígenas para que avanzaran sus intereses, que iban desde resistir al trabajo forzado hasta mantener sus prácticas agrícolas tradicionales. Para la década de 1930, la producción alimenticia doméstica se había incrementado notablemente debido a que a principios del siglo las autoridades estatales se unieron a los pequeños agricultores para promover la agricultura de consumo doméstico. Portuguese abstract: Grande parte da história da agricultura dos séculos dezenove e vinte na América Latina tem sido dominada por estudos sobre produtos de exportação e economias. Entretanto mercados domésticos abastecidos por pequenos agricultores foram tão quanto importantes para o desenvolvimento nacional. Utilizando a Guatemala como estudo de caso para a América Latina, este artigo examina os desafios enfrentados por produtores rurais dos mercados local, regional e nacional. Durante o período nacional, a preocupação esporádica das autoridades do Estado para com a agricultura doméstica gerou oportunidades para pequenos agricultores indígenas, que puderam avançar seus objetivos que iam desde a resistir ao trabalho forçado a manter suas práticas tradicionais de agricultura. Em 1930, a produção de comestíveis já haviam crescido significativamente. Isso porque no início do século autoridades do Estado se juntaram aos pequenos agricultores para promover a agricultura de fins domésticos.